Dairy Milk Quality After Foot and Mouth Disease in Ternak Sukses Bersama, Kediri Regency - Dameanti, Fidi Nur Aini Eka Puji; Assyifa, Fraya; Kamulyan, Ujiati; Delivery, Rheina Yesi Octa; Safri, M. Ali AkramSyah; Ompusunggu, Meifi Mariana; Sutrisno, Rahayu (Universitas Airlangga, 2024)
Background: Milk, a nutrient-rich substance obtained from udder secretions, can suffer quality degradation due to factors like disease-causing microorganisms. Foot and Mouth Disease (FMD), an acute viral infection affecting cloven-hoofed animals, can severely impact milk production and quality. Purpose: This study aims to analyze the quality of milk from dairy cattle following the FMD outbreak, as FMD not only reduces milk yield but also alters its composition, affecting consumer preferences and farmer income. Method: Milk quality tests were conducted on cattle following the FMD outbreak with each 50 ml sample stored in an icebox and analyzed using a calibrated Lactoscan tool. The analysis covered fat, solid-non-fat (SNF), density, lactose, salts, protein, temperature, freezing point, added water, total solids, and pH levels. The study received consent from local authorities and breeders. Results: The analysis of cow milk post Foot and Mouth Disease (FMD) outbreak reveals significant variability in milk composition, affecting quality and processing, with many falling below or above standard thresholds for fat content, SNFs, protein content, freezing point, and added water, while all samples had a pH level outside the acceptable range. Conclusion: Quality of dairy milk from dairy cattle after FMD outbreaks show decreasing of fat content in five milk samples, four samples in solid non fat, three samples in protein, nine samples in freezing point, eight samples in added water, and all samples fell outside the acceptable pH range.